An Updated Model Does Not Reveal Sex Differences in Patellofemoral Joint Stress during Running - Laura Jacobson; C. Nathan Vannatta; Catherine Schuman; Thomas W. Kernozek (International Journal of Sports Physical Therapy)
# Background